Association of Age at Marriage, Early Childbearing, Use of Contraceptive Methods and Reproductive Health Consequences Among Mishing Tribal Women of Assam, Northeast India - Nitamoni Bharali (Light House Polyclinic Mangalore, 2021)
Background: Reproductive health implies to have maintained reproductive capabilities to reproduce the freedom to decide if, when and how often to do so. Objectives: The aim of the present investigation was to determine the associations of early age at marriage, early childbearing, use of contraceptive methods and reproductive health consequences among Mishing tribal women. Methods: The community-based cross-sectional investigation was carried out among 1056 Mishing tribal women aged between 15-45 years residing in Lakhimpur district, Assam. The data on family planning, contraceptive use, duration of pregnancy, total conceptions, total number of live births, miscarriage, abortion (induced) and complication related to reproductive system were obtained using pre-structured schedule and interview method by household visits. Results: More than half of the Mishing women were encountering with various reproductive health related complications, where 54.45%, 12.25% and 5.87% of women were experienced miscarriage, abortion and still birth, respectively. BLR analysis showed that early marriage (e.g., <15 years and 16-20 years), family planning methods, oral contraceptive use and reproductive complications were found to have significant association with miscarriages (p<0.05). The higher risk associations were found in age at first child (≤18 years), oral contraceptive use and reproductive complications with stillbirths (p<0.05). Similarly, risk of induced abortion was observed to be higher with oral contraceptive use, family planning method and <Rs. 10000 family income (p<0.05). Conclusion: There are urgent requirements for target-oriented healthcare programs and strategies for better reproductive health, family planning methods, awareness about child gap, adverse reproductive complications and abortion related issues to improve the reproductive health.